Bioconversão microbiana de penas de frango como estratégia para a produção de hidrolisados proteicos bioativos - Callegaro, Kelly (2018)
Feathers are by-products rich in recalcitrant proteins named keratins, generated in enormous amounts by the poultry industry. There is an increasing demand for economic and ecologically appropriate methods for feathers management. Microbial bioconversion has been investigated as a promising strategy for the recycling of feathers, since, along with the degradation of these keratinous materials, bioprocessing can result into added-value products. Production of protein hydrolysates is of particular scientific and technological interest since proteins can be precursors of peptides with biological activities. Only recently the bioactive potential of feather/keratin hydrolysates has been described. This study evaluated feather degradation, protease production and bioativities of feather hydrolysates (FH) produced through submerged cultivations with the keratinolytic bacteria Bacillus sp. CL18, Bacillus sp. CL33A and Bacillus sp. CL14. In feather broth (10 g/L of feathers), Bacillus sp. CL18 produced greater proteolytic activity, degrading the feathers more efficiently, and the resulting FHs showed high antioxidant activities. With increasing feather concentration in the culture medium (10 to 50 g/L), Bacillus sp. CL18 produced higher proteolytic activity after five days of cultivation in medium containing 30 g/L of feathers, and the highest soluble protein content was detected (9.02 mg/mL) after five days of cultivation in medium with 40 g/L of feathers. The FHs displayed antioxidant activities, measured by the scavenging of 2,2-diphenyl-1- picrylhydrazyl (DPPH) and 2,2'-azino-bis-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS) radicals, Fe2+-chelating ability, and reducing power. Antihypertensive and antidiabetic activities, in vitro, were also demonstrated by inhibition of angiotensin-I converting enzyme (ACE) and the enzyme dipeptidyl peptidase IV (DPP IV), respectively. FH obtained through cultivation of Bacillus sp. CL18 in feather broth (40 g/L of feathers) for five days, and subsequently lyophilized, presented half-maximal effective/inhibitory concentrations of 5.39 mg/mL, 15.12 mg/mL, 10.50 mg/mL, 61 mg/mL and 1.52 mg/mL in the ABTS, DPPH, Fe2+-chelating, ACE- and DPP IVinhibitory assays, respectively. Production of microbial proteases with potential applications in biocatalysis, and of bioactive protein hydrolysates, indicates microbial conversion as an appropriate and eco-friendly technology for feathers reclamation and valorization.